Testicular torsion in the inguinal region in an extremely low birth weight infant - Yu Jin Jung; Jae Min Chung (Korean Pediatric Society, 2010)
Testicular torsion is rare in newborn infants. However, its frequency has increased, most of which are reported in full-term infants. We diagnosed and treated testicular torsion in an extremely low birth weight infant (ELBWI). A 2×2 cm red mass was palpable in the left groin of a 24-week-old, 745 g, male newborn at 23 days of age. Left testicular torsion was diagnosed, and emergent orchiopexy was performed. Careful physical examination is needed in cases suspicious of testicular torsion in ELBWIs with cryptorchidism. Moreover, early diagnosis and emergent exploration are necessary to prevent complications such as the risk of anorchia.